2015
DOI: 10.1074/jbc.m115.682179
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Fe-S Cluster Protein Maturation and Iron Regulation Are Independent of the Mitochondrial Erv1/Mia40 Import System

Abstract: Background:The mitochondrial sulfhydryl oxidase Erv1 is implicated in cytosolic iron-sulfur protein maturation and iron regulation. Results: An erv1 yeast strain used in previous iron metabolism studies is glutathione-deficient, and erv1/mia40 mutants with sufficient glutathione do not exhibit iron-related defects. Conclusion: Iron homeostasis is independent of Erv1/Mia40 function. Significance: The unexplained role of Erv1 in yeast iron metabolism is resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The export of this structure is mediated by ABCB7 in cooperation with ALR, an FAD-dependent sulfhydryl oxidase. The implication of ALR is, however, still a matter of debate, as a study in yeast could not show impaired cytosolic iron–sulfur cluster assembly [ 6 ]. The mitochondrial machinery can synthesize [2Fe–2S] or [4Fe–4S] clusters and incorporate these into the appropriate apoproteins (Fig.…”
Section: Mitochondrial Iron–sulfur Biosynthesis (Isc)mentioning
confidence: 99%
“…The export of this structure is mediated by ABCB7 in cooperation with ALR, an FAD-dependent sulfhydryl oxidase. The implication of ALR is, however, still a matter of debate, as a study in yeast could not show impaired cytosolic iron–sulfur cluster assembly [ 6 ]. The mitochondrial machinery can synthesize [2Fe–2S] or [4Fe–4S] clusters and incorporate these into the appropriate apoproteins (Fig.…”
Section: Mitochondrial Iron–sulfur Biosynthesis (Isc)mentioning
confidence: 99%
“…Interestingly, glutathione production in the prothoracic gland is also required for steroidogenesis (Enya et al, 2017 ). The possibility that glutathione supports Fe-S cluster biosynthesis in this tissue should be considered (Song et al, 2006 ; Auchère et al, 2008 ; Qi et al, 2013 ; Ozer et al, 2015 ).…”
Section: Fe-s and Moco Enzymesmentioning
confidence: 99%
“… Sipos et al (2002) demonstrated in their work that while proteins with iron-sulfur clusters can be assembled under anaerobic conditions in the mitochondria of S. cerevisiae, maturation of iron-sulfur proteins in its cytosol requires the presence of glutathione even if the media is maintained anaerobic. It has been shown that glutathione protects iron-sulfur proteins from oxidative stress, thereby allowing for their successful maturation ( Ozer et al, 2015 ). Therefore, ADP1 cells were induced for ER synthesis under anaerobic conditions in the presence of 1 mM glutathione for 12 h, followed by incubation under anaerobic or aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%